2012
DOI: 10.5468/kjog.2012.55.10.777
|View full text |Cite
|
Sign up to set email alerts
|

A case of primitive neuroectodermal tumor of the ovary

Abstract: Peripheral primitive neuroectodermal tumor (PNET) is a small round tumor belonging to the PNET/Ewing's sarcoma family classified based on location in the body. There have been a small number of case reports of PNET arising in the ovary. We present extremely rare case of PNET of the ovary occurring in a 32-year-old pregnant woman, which was detected during her second Cesarean section. She had a past history of oophorectomy due to a huge mature solid teratoma in left ovary during her first Cesarean section. She … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The treatment for ES includes surgical resection, chemotherapy, and radiotherapy. However, despite this multi-modal therapeutic approach, overall survival for the patients remains low, as reported in studies by Mulsow et al 35 and Abboud et al 36 Kuk et al 30 reported an overall survival in ovarian ES patients ranging from 10.8 to 36 months. Moreover, owing to the rarity of ovarian ES, standard effective treatment guidelines do not exist.…”
Section: Discussionmentioning
confidence: 98%
“…The treatment for ES includes surgical resection, chemotherapy, and radiotherapy. However, despite this multi-modal therapeutic approach, overall survival for the patients remains low, as reported in studies by Mulsow et al 35 and Abboud et al 36 Kuk et al 30 reported an overall survival in ovarian ES patients ranging from 10.8 to 36 months. Moreover, owing to the rarity of ovarian ES, standard effective treatment guidelines do not exist.…”
Section: Discussionmentioning
confidence: 98%
“…PNETs are uncommon entities especially for the female genital tract and the ovaries are the most common location ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ) . It seems that the exact age for non-skeletal ES is not clear, but cases in the literature were seen between the second and third decades of the life.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between ES of the ovary and other tumors is made through immunohistochemistry studies. As seen in Table 2 , ( 12 , 13 , 14 , 15 , 24 ) on immunohistochemistry, diffuse membranous positivity for MIC2 (CD99), CD56 (neural cell adhesion molecule), HMW CK and FL1 led to the consideration of PNETs. Negativity for epithelial markers such as CK, EMA, desmin, and WT-1 led to the consideration of desmoplastic small round cell tumors (SRCTs).…”
Section: Discussionmentioning
confidence: 99%
“…Various literatures on ES focus mainly on rare sites such as craniofacial, hands and feet, gastrointestinal organs, and spinal masses. There have been case reports on ES on the ovary, [3] kidney, [4] and phalanges of hand. [5]…”
Section: Introductionmentioning
confidence: 99%